The role of a vaccine booster for a fractional order model of the dynamic of COVID-19: a case study in Thailand - Puntipa Pongsumpun; Puntani Pongsumpun; I‐Ming Tang; Jiraporn Lamwong (Scientific Reports, 2025)
This article addresses the critical need for understanding the dynamics of COVID-19 transmission and the role of booster vaccinations in managing the pandemic. Despite widespread vaccination efforts, the emergence of new variants and the waning of immunity over time necessitate more effective strategies. A fractional-order mathematical model using Caputo-Fabrizio derivatives was developed to analyze the impact of booster doses, symptomatic and asymptomatic infections, and quarantine measures. The model incorporates real epidemic data from Thailand and includes a sensitivity analysis of parameters influencing disease spread. Numerical results indicate that booster vaccinations significantly reduce transmission rates, and the model's predictions align well with the observed data. The basic reproduction number was determined to evaluate disease control, showing that a sustained vaccination campaign, including booster doses, is essential to maintaining immunity and controlling future outbreaks. The findings underscore the importance of ongoing vaccination efforts and provide a robust framework for policymakers to design effective strategies for pandemic control.
Keywords: Fractional Differential Equations Solutions; COVID-19 epidemiological studies; Mathematical and Theoretical Epidemiology and Ecology Models